Twenty Years of Marine Carbon Cycle Observations at Devils Hole Bermuda Provide Insights into Seasonal Hypoxia, Coral Reef Calcification, and Ocean Acidification - Bates, Nicholas R. (Frontiers in Marine Science, 2017)
Open–ocean observations have revealed gradual changes in seawater carbon dioxide (CO2) chemistry resulting from uptake of atmospheric CO2 and ocean acidification (OA), but, with few long–term records (>five years) of the coastal ocean that can reveal the pace and direction of environmental change. In this paper, observations collected from 1996 to 2016 at Harrington Sound, Bermuda, constitute one of the longest time–series of coastal ocean inorganic carbon chemistry. Uniquely, such changes can be placed into the context of contemporaneous offshore changes observed at the nearby Bermuda Atlantic Time-series Study (BATS) site. Onshore, surface dissolved inorganic carbon (DIC) and partial pressure of CO2 (pCO2; >10% change per decade) have increased and OA indicators such as pH and calcium carbonate (CaCO3) saturation state (Ω) decreased from 1996–2016 at a rate of two to three times that observed offshore at BATS. Such changes, combined with reduction of total alkalinity over time, reveal a complex interplay of biogeochemical processes influencing Bermuda reef metabolism, including net ecosystem production (NEP=gross primary production–autotrophic and heterotrophic respiration) and net ecosystem calcification (NEC=gross calcification–gross CaCO3 dissolution). These long–term data show ae seasonal shift between wintertime net heterotrophy and summertime net autotrophy for the entire Bermuda reef system. Over annual time-scales, the Bermuda reef system does not appear to be in trophic balance, but rather slightly net heterotrophic. In addition, the reef system is net accretive (i.e., gross calcification > gross CaCO3 dissolution), but there were occasional periods when the entire reef system appears to transiently shift to net dissolution. A previous five–year study of the Bermuda reef suggested that net calcification and net heterotrophy have both increased. Over the past twenty years, rates of net calcification and net heterotrophy determined for the Bermuda reef system have increased by 30%, most likely due to increased coral nutrition occurring in concert with increased offshore productivity in the surrounding subtropical North Atlantic Ocean. Importantly, this long–term study reveals that other environmental factors can mitigate against the effects of ocean acidification on coral reef calcification, at least over the past couple of decades.